Clot structure and fibrinolytic potential in patients with post thrombotic syndrome. (January 2016) - Bouman, A.C.; McPherson, H.; Cheung, Y.W.; ten Wolde, M.; ten Cate, H.; Ariëns, R.A.S.; ten Cate-Hoek, A.J.
Abstract: Introduction: Post-thrombotic syndrome (PTS) is a chronic sequel of deep vein thrombosis (DVT). The clot structure and fibrinolytic potential in PTS is currently unknown. Objective: To assess the fibrinolytic potential and clot structure in patients with PTS. Materials and methods: Patients with a history of DVT were included in a case–control study: patients with PTS (cases n = 30) and without PTS (controls n = 30), and 30 apparently healthy individuals (HI) without venous thromboembolism (VTE) or venous insufficiency were enrolled. Fibrinolysis and clot structure were assessed by turbidimetric assays, permeation, and confocal microscopy. Fibrinogen was measured by Clauss and fibrinogen γ′ by ELISA. Results: We observed a significant trend of decreasing maximum turbidity from HI (median 0.52 [IQR 0.46–0.62]), to controls (0.49 [IQR 0.41–0.55]), to cases (0.46 [IQR 0.39–0.49]) p = 0.020. Fibrinogen was lower in patients (cases and controls) (3.69 g/L [IQR 3.31–4.26]) compared to HI (4.17 [IQR 3.69–4.65]) p = 0.041. Patients with recurrent VTE had lower maximum turbidity and lower permeation than patients with one episode of VTE; (0.31 [IQR 0.25–0.39] versus 0.38 [IQR 0.34–0.44] p = 0.008) and (6.0 × 10 − 9 /cm 2 [IQR 5.1–7.9] versus 7.7 × 10 − 9 /cm 2 [IQR 6.0–10.0] p = 0.047) respectively, at equal fibrinogen levels. There were no differences in lysis time, confocal microscopy, or fibrinogen γ′. Conclusions: Lower maximum turbidity, indicating a tendency towards thinner fibres and denser clots, was found in patients with PTS as well as in patients with recurrent VTE. Fibrinogen levels did not explain these differences in clot structure. The abnormal clot structure may contribute to the increased thrombotic risk profile in patients with PTS. Highlights: We found indications of thinner fibres and denser clots, in patients with PTS. Tendency towards denser clots with thinner fibres was also found in recurrent VTE. Denser clots might predispose to PTS in itself, but also via recurrent DVT.